2014
DOI: 10.1002/ange.201407144
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Giant Molecular Solomon Link from 30 Subcomponents

Abstract: The synthesis of topologically complex structures, such as links and knots, is one of the current challenges in supramolecular chemistry. The so‐called Solomon link consists of two doubly interlocked rings. Despite being a rather simple link from a topological point of view, only few molecular versions of this link have been described so far. Here, we report the quantitative synthesis of a giant molecular Solomon link from 30 subcomponents. The highly charged structure is formed by assembly of 12 cis‐blocked P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Finally, by exhaustive enumeration of braid patterns, we found that only few and specific types of additional knots might be addressable by using either a larger number of helical templates, or few templates but with wavy or S-shaped geometries 34 , either rigid 37 or with flexible termini 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, by exhaustive enumeration of braid patterns, we found that only few and specific types of additional knots might be addressable by using either a larger number of helical templates, or few templates but with wavy or S-shaped geometries 34 , either rigid 37 or with flexible termini 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The challenges encountered in designing and then obtaining knotted molecular architectures lie in the numerous concurrent physico-chemical mechanisms that need to be balanced and steered. These include the length, thickness, intrinsic curvature and relative spatial orientation of the ligands and, above all, a judicious choice of the target topology 32 37 . Not all knot types are, in fact, equally designable neither a priori nor in practice 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Two methyl groups were intentionally introduced to increase the steric effect of the bpy groups, which can tune the recognition of bpy groups with different metal ions. [132]. The combination of bis-chelating unit bridged arene-Ru II acceptor and a bifunctional pyridine linker often generate the molecular rectangles.…”
Section: Solomon Linksmentioning
confidence: 99%
“…Synthesis of Solomon link 69-Cu I Pt II (all Ph rings attached to P atom are omitted for clarity)[132].…”
mentioning
confidence: 99%
“…[1] In particular, coordination-driven self-assembly has witnessed significant growth, with the construction of ab road array of metallosupramolecules of increasing complexity. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] TheS tar of David, ah exagram (or figure composed of two equilateral triangles) recognized as the symbol of Jewry,has been explored extensively across science, mathematics,e ngineering,t echnology,b usiness,h istory,a nd art. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] TheS tar of David, ah exagram (or figure composed of two equilateral triangles) recognized as the symbol of Jewry,has been explored extensively across science, mathematics,e ngineering,t echnology,b usiness,h istory,a nd art.…”
mentioning
confidence: 99%